A behavioral model of international channel relationships. Issue 4 (2nd October 2017) - Hirshberg, Ronit Segal; Shoham, Aviv
ABSTRACT: Purpose: The main purpose of the study is to fill the existing gap in international relationship marketing (IRM) literature by developing and testing empirically a comprehensive conceptual model of firms' relationship with their marketing channels in export markets. Whereas concepts such as power, conflicts, trust, commitment, and communication have been shown to be related to the economic success of interfirm cooperation in general and buyer–seller relations in particular, the need for a comprehensive model is often expressed in the literature. Methodology/approach: The authors combine commitment-trust theory with resource-based and knowledge-based view perspectives to develop a new comprehensive conceptual model of firms' relationship with their marketing channels in export markets. Data from 104 strategic business units in Israel was used to test the model empirically. Findings: Notably, the model tested explained a higher percentage of the variance in performance. The findings suggest that noncoercive power enhances relationship quality (i.e., communication, trust, and commitment), which in turn improve cooperation and export performance. Conflict had a negative effect on relationship quality. In addition, cooperative conflict management strategies had a positive moderating effect on the conflict— relationship quality link, whereas competitive conflict management strategies had a negative moderating effect on the impact of conflict on relationship quality. Finally, the results suggest that there are strong positive relations between communication and trust and between trust and commitment. Research implications: The research develops and tests empirically a conceptual comprehensive model of firms' relationship with their marketing channels in export markets by including major performance drivers. The model incorporates conflict management strategies and combines commitment-trust theory with resource-based view (RBV) and knowledge-based view (KBV), an innovative combination with great explanatory potential. Based on the findings, there is sufficient support for using the suggested model as a new integrative behavioral model that explains channel relationships. Practical implications: The results indicate that managers should use noncoercive power and cooperative conflict management strategies in order to positively affect relationship quality (i.e., communication, trust, and commitment), which in turn enhances cooperation and export performance. Originality/value/contribution: The suggested research model presents a novel combination of existing relationship marketing (RM) knowledge with the limited IRM knowledge into a comprehensive IRM model. It includes new relationships beyond those studied before. Integrating and synthesizing results from a large body of conceptual and empirical literature led to the final model. Accordingly, it contributes elements of newness. First, the model includes major antecedents of performance. To the best of our knowledge, this is the most comprehensive model of firms' relationship with their international marketing channels in export markets. Second, there are almost no studies investigating conflict management strategies neither in RM nor in IRM models. Accordingly, a contribution of this research is incorporating conflict management strategies within the model and analyzing their effects.